Molecular validation of pathogen‐reduction technologies using rolling‐circle amplification coupled with real‐time PCR for torquetenovirus DNA quantification. Issue 5 (12th August 2021) - Focosi, Daniele; Macera, Lisa; Spezia, Pietro Giorgio; Ceccarelli, Francesca; Lanza, Maria; Maggi, Fabrizio
Abstract: Background: Pathogen reduction technologies (PRT) based on nucleic‐acid damaging chemicals and/or irradiation are increasingly being used to increase safety of blood components against emerging pathogens, such as convalescent plasma in the ongoing COVID‐19 pandemic. Current methods for PRT validation are limited by the resources available to the blood component manufacturer, and quality control rely over pathogen spiking and hence invariably require sacrifice of the tested blood units: quantitative real‐time PCR is the current pathogen detection method but, due to the high likelihood of detecting nonviable fragments, requires downstream pathogen culture. We propose here a new molecular validation of PRT based on the highly prevalent human symbiont torquetenovirus (TTV) and rolling circle amplification (RCA). Materials and methods: Serial apheresis plasma donations were tested for TTV before and after inactivation with Intercept® PRT using real‐time quantitative PCR (conventional validation), RCA followed by real‐time PCR (our validation), and reverse PCR (for cross‐validation). Results: While only 20% of inactivated units showed significant decrease in TTV viral load using real‐time qPCR, all donations tested with RCA followed by real‐time PCR showed TTV reductions. As further validation, 2 units were additionally tested with reverse PCR, which confirmed absence of entire circular genomes. Discussion: We have described and validated a conservative and easy‐to‐setup protocol for molecular validation of PRT based on RCA and real‐time PCR for TTV.